Eksplorasi Potensi Produk Unggul Desa Untuk Peningkatan Kesejahteraan Ekonomi Keluarga Desa Senang Hati - Subekti, Rini; Riana, Kurnia Endah; Ginting, Ginta; Harsasi, Meirani; Andriyansah, Andriyansah (Abdimas Indonesian Journal, 2024)
This community service activity aims to provide entrepreneurship counseling to the community so that they can take advantage of the main opportunities to explore the potential (resources) that exist. One of the opportunities that can have a direct economic impact on the community is to explore and optimize the role of the creative industry where the community can create, explore the uniqueness, potential advantages of resources and local wisdom that are owned so as to produce products that have added value. Entrepreneurship counseling in Senang Hati Village, Malimping Sub-district, Lebak Regency, Banten Province, is expected to open insights and knowledge about the essence of utilizing opportunities to creatively process the potential resources owned. Thus, the community can increase their capacity to start a profitable business. To achieve this goal, it is necessary to provide knowledge about the preparation of marketing strategies and product diversification (market segmentation, product development, promotion, branding, packaging).